2004
DOI: 10.1007/s00403-004-0458-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships of three differently substituted 2,7,12,17-tetrakis-(�-methoxyethyl) porphycene derivatives in vitro

Abstract: The subcellular localization, efficacy and photooxidative mechanism of three new photosensitizing porphycenes (HexoTMPn, PeloTMPn, CpoTMPn) for photodynamic therapy with different substituents at position 9 of the tetrapyrrole macrocycle were investigated in vitro using different human skin-derived cell lines (HaCaT, SCL I, SCL II) with the aim of customizing the side-chain chemistry to accelerate cellular uptake and so enhance photodynamic activity. Cells were incubated with a porphycene and costained with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Consequently, the diffusion distance during the lifetime of 1 O 2 under these conditions would be around 100 nm, much longer than estimates arising from the studies using cell populations described above. These results on single cells are in agreement with results of studies where isotope effects were found for of 1 O 2 photosensitization in cells when H 2 O was replaced by D 2 O in the media (44–49). Such effects would not be expected if the 1 O 2 lifetime was limited by reaction rather than solvent‐induced deactivation.…”
Section: Lifetime Of Singlet Oxygen In Cellssupporting
confidence: 91%
“…Consequently, the diffusion distance during the lifetime of 1 O 2 under these conditions would be around 100 nm, much longer than estimates arising from the studies using cell populations described above. These results on single cells are in agreement with results of studies where isotope effects were found for of 1 O 2 photosensitization in cells when H 2 O was replaced by D 2 O in the media (44–49). Such effects would not be expected if the 1 O 2 lifetime was limited by reaction rather than solvent‐induced deactivation.…”
Section: Lifetime Of Singlet Oxygen In Cellssupporting
confidence: 91%
“…chemical design and prediction of biological activity, only few QSAR studies on pharmacokinetics, subcellular localization, and tumor photosensitization of new PSs have been published [42, [227][228][229][230][231][232][233], and also very limited information about QSAR of porphycene PSs is available [234][235][236].…”
Section: Photobiological Activity In Vitromentioning
confidence: 99%
“…We reported recently on a series of porphyrin and chlorin based bile acid conjugates (123)(124)(125)(126) to impart greater selectivity and specificity on the photosensitizer for the treatment of esophageal cancer. 93 Chronic esophageal exposure to bile acids in patients with gastro-esophageal reflux disease is associated with the development of Barrett's metaplasia and associated molecular markers of inflammation which have been shown to support transformation, initiation and progression of tumor development.…”
Section: Porphyrin-bile Acid Conjugatesmentioning
confidence: 99%
“…41). 126 HexoTMPn 187 127 The triplet (Φ T = 0.33) and singlet oxygen (Φ Δ = 0.23) quantum yields of the former are comparable to that of other porphycenes, but much lower in comparison to the porphyrin isomer TPP (Φ Δ = 0.68). In the case of 191, fluorescence is inhibited by the internal heavy-atom effect and the triplet and singlet oxygen quantum yields are enhanced (Φ T = Φ Δ = 0.78).…”
mentioning
confidence: 91%